2013
DOI: 10.18172/cig.1064
|View full text |Cite
|
Sign up to set email alerts
|

Respuesta hidrológica en los medios semiáridos : las cuencas experimentales en la Sierra de Picarcho, Murcia

Abstract: l. Introducción El conocimiento de la respuesta hidrológica de una cuenca hidrográfica es necesario para distintos fines, desde la estimación de los caudales generados por las tormentas hasta la evaluación del impacto que producen los cambios de uso del suelo en el ciclo del agua (Grayson et al.,1992).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 8 publications
1
6
0
Order By: Relevance
“…For this reason, the locations of runoff-contributing areas show large spatial variability, ranging from small, degraded areas close to the channel to the entire catchment (García-Ruiz et al, 2005). This spatial variability has also been reported from other catchments under different Mediterranean environments, including the Guadalperalón catchment under Dehesa land use (Ceballos and Schnabel, 1998;Ceballos, 1999), the Vallcebre catchment with abandoned, reforested bench-terraced fields (Llorens and Gallart, 1992;Gallart et al, 2005), and the Sierra de Picarcho catchments (SE Spain) with an open shrub cover (Castillo et al, 2000).…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…For this reason, the locations of runoff-contributing areas show large spatial variability, ranging from small, degraded areas close to the channel to the entire catchment (García-Ruiz et al, 2005). This spatial variability has also been reported from other catchments under different Mediterranean environments, including the Guadalperalón catchment under Dehesa land use (Ceballos and Schnabel, 1998;Ceballos, 1999), the Vallcebre catchment with abandoned, reforested bench-terraced fields (Llorens and Gallart, 1992;Gallart et al, 2005), and the Sierra de Picarcho catchments (SE Spain) with an open shrub cover (Castillo et al, 2000).…”
Section: Discussionmentioning
confidence: 57%
“…For the above reasons, the number of experimental catchments has increased markedly in recent years (Walling, 1991), particularly in Spain, where they are found in contrasting environments ranging from areas with a semiarid Mediterranean climate (Castillo et al, 2000;Cantón et al, 2004), to high Pyrenean mountains (Alvera and García-Ruiz, 2000), mid-altitude mountains (Gallart et al, , 2002Llorens et al, 1997;Arnáez et al, 1999;García-Ruiz et al, 2000Serrano-Muela et al, 2008), and dehesa environments (Ceballos and Schnabel, 1998).…”
mentioning
confidence: 99%
“…The data record in this area extends from 1997 until 2003. Results of the studies carried out in this area using this set-up can be found in Gómez-Plaza (2000), Gómez-Plaza et al (2000) and Castillo et al (2000Castillo et al ( , 2003.…”
Section: Venta Del Olivo Area (Vo)mentioning
confidence: 99%
“…At the catchment level, sediment delivery measurements at three catchments (two in a burnt area and one in an unburnt area) in a monitored area on limestone material of El Picarcho (Murcia) (Castillo et al, 2000) resulted in average values of 0Á034, 0Á011 and 0Á015 t ha À1 y À1 , respectively. During five years of monitoring only four events produced sediment transport at the outlet of the catchments and these events were concentrated in two years (Boix-Fayos et al, submitted).…”
Section: Field Datamentioning
confidence: 99%